The relationships between facilitating conditions, internal beliefs, attitute and lecturers' trend of using iTa'leEM in International Islamic University Malaysia - Siti Aminah binti Abd Wahab (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The emergence of e-learning and the Learning Management System (LMS) have created a gap between the acceptance of the technology by higher learning institutions (HLI) and the integration of the technology by instructors in their teaching and learning (T&L) approaches. This study aims to identify possible factors that may predict the instructors' trend of using LMS in their T&L activities. Underpinned by the Technology Acceptance Model (TAM) (Davis, 1985), three internal factors (i.e., attitude, perceived usefulness and perceived ease of use) and one external factor (i.e., facilitating conditions) were postulated as having direct and indirect relationships with the lecturers' use of LMS. A cross-sectional survey was conducted among the academic staff of the International Islamic University Malaysia (IIUM) in the Gombak and Kuantan campuses. A total of 165 academic staff from 12 kulliyyahs participated in the study. Analyses on the direct and indirect associations between the lecturers' trend of using the university's LMS (i.e., iTa'LeEM) and its predicting factors indicate that all hypothesised correlations are supported, thus confirming the applicability of TAM as a theoretical framework in addressing the issue of usage and acceptance of iTa'LeEM among IIUM lecturers. Furthermore, a regression analysis on the overall relationship between the variables has identified only perceived usefulness as a significant predictor that is able to predict the lecturers' trend of using iTa'LeEM. Additionally, the lecturers' use of iTa'LeEM across different teaching fields are significantly varied. Overall, the results seem to imply that the issues regarding the low utilisation of institutional LMS exist in IIUM. As the usage patterns varies by kulliyyah, low adoption of LMS is partly due to a stronger preference towards a more traditional method (i.e. face-to-face) and the lack of organizational and technical support (facilitating conditions) from the university authorities. Lastly, recommendations are made for further studies in this area as well as for the improvement of iTa'LeEM usage by its administrators. For academic purposes, the extension of TAM with other technology acceptances theories by focusing on perceived usefulness as the central construct in a longitudinal study, is suggested. While for LMS administrators, the researcher proposes for the improvement of facilitating conditions to enhance the lecturers' use of advance features in the system.